Reinterpreting Imperial-Oriental and Liberal Issues in E.M. Forster’s A Passage to India: A Marxist Perspective - Ali, Fares Mohammed S; Ubale, Anand (South Asian Journal of Social Sciences and Humanities, 2023)
The current research article highlighted the imperial-oriental and liberal issues included in E.M.Forster’s A Passage to India that was considered as one of the colonial discourses. Forster criticizes properly the British imperialism according to the book incidents. To explore the above issues critically, the researcher focused on the concept of hegemony as one of the major arguments of the Marxist approach. This concept was first articulated by the prominent Marxist theorist Antonio Gramsci who divided it into two forms namely the coercive hegemony and the consent one. In this regard, it is seen that the imperial values were represented by the coercive hegemony, while the oriental discussions were represented the consent hegemony. Based on the book events, the British see themselves as superior while the native Indians are inferior and this classification comes under the consent hegemony according to Gramsci’s allegations. This research work aimed to reinterpret the imperial-oriental and liberal issues embodied in Forster’s book, A Passage to India in the light of the Marxist perspective.